THE EFFECT OF GOLD PRICES, EXCHANGE RATES, AND COMPANY EARNINGS ON STOCK PRICES IN AUTOMOTIVE AND COMPONENT SECTOR COMPANIES WITH INFLATION AS A MEDIATING VARIABLE - Sella Agustin; Lestari Wuryanti; Muhammad Irfan Pratama (Yayasan Multidimensi Kreatif, 2026)
This study aims to examine the influence of gold prices, exchange rates, and company earnings on stock prices in automotive and component sector companies with inflation as a mediating variable during the 2020–2024 period. This study uses a quantitative approach. The research population is automotive and component sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used the purposive sampling method so that 8 companies were obtained as research samples. The analysis method used was panel data regression with the help of EViews12 software. The results of the study show that the price of gold does not have a significant effect on the stock price, the exchange rate has a significant effect on the stock price, while the company's income does not have a significant effect on the stock price. In addition, inflation has been shown to have a significant effect on stock prices. However, based on the results of mediation analysis and sobel tests, inflation has not been proven to play a mediating variable in the relationship between gold prices, exchange rates, and company earnings to company stock prices in the automotive and component sectors. These findings show that stock price movements in the automotive and component sectors are more influenced by macroeconomic factors directly, especially exchange rates and inflation, than through indirect influence mechanisms.